2012
DOI: 10.4490/algae.2012.27.4.283
|View full text |Cite
|
Sign up to set email alerts
|

The distribution and ecological factors of aerial algae inhabiting stoneworks in Korea

Abstract: The physico-chemical and environmental factors of stoneworks were examined from March 2009 to October 2010, and aerial algae living on 24 stoneworks in Korea were identified. Fifty aerial algae were found in 24 stoneworks. Of the 50 taxa, 30 taxa were cyanophytes, 16 taxa were bacillariophytes, 3 taxa were chlorophytes, and 1 taxon was a xanthophyte. Nine species, including Aphanocapsa rivularis, which is known to only live in aquatic conditions, inhabited both aquatic and aerial environments. Synechococcus ae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
(13 reference statements)
0
7
0
Order By: Relevance
“…A total of 105 partial 16S rRNA gene sequences were obtained, and they were divided into 30 generic types of six main cyanobacterial order clades [ 40 ]. This means that the terrestrial cyanobacterial diversity at the University of the Ryukyus campus is more diverse than in locations from other surveys, including in India [ 4 , 5 , 6 , 7 ], South Korea [ 21 , 22 ], the main Haiwaiian islands [ 14 ], Brazil, and Mexico [ 12 , 13 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 105 partial 16S rRNA gene sequences were obtained, and they were divided into 30 generic types of six main cyanobacterial order clades [ 40 ]. This means that the terrestrial cyanobacterial diversity at the University of the Ryukyus campus is more diverse than in locations from other surveys, including in India [ 4 , 5 , 6 , 7 ], South Korea [ 21 , 22 ], the main Haiwaiian islands [ 14 ], Brazil, and Mexico [ 12 , 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…The diversity distribution of particular cyanobacteria on monuments in urban regions are thought to be related mostly to environmental conditions of the climate, such as water availability and air circulation, and to the position and orientation of the hard surface [ 43 ]. Correlations among other environmental factors have been tested to identify other factors that could substitute for the effects of humidity and light intensity [ 22 ]. To examine such environmental factors, it is likely that selecting a few sampling points in the Nishihara campus of the University of the Ryukyus should be enough due to the very high diversity of terrestorial cyanobacteria at this location.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analyses of physico-chemical environmental factors, such as the surface temperature of the substrates, light intensity, and humidity, were conducted on all the sampling dates (Song et al 2012). The temperature was measured Guiry (2014), 6 species of the genus Spongiococcum were reported, but only S. tetrasporum has been accepted taxonomically in this genus.…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, G. acuminatum is an opportunistic diatom taxon, which thrives in nutrient-poor lake ecosystems. The species is sometimes found in aerial habitats (Song et al, 2012) in dry evaporative lake conditions (Pinilla, 2010) and has been reported as abundant in shallow water and habitats with high light exposure (Bothwell et al, 1993;Michelutti et al, 2001). In particular, it is generally related to rich macrophyte growth and calm water (Michelutti et al, 2001).…”
Section: Gomphonema Spp: Modern Habitat and Seasonal Biomass Productionmentioning
confidence: 99%